Serum soluble tumour necrosis factor receptor-2 (sTNFR2) as a biomarker of kidney tissue damage and long-term renal outcome in lupus nephritis. (4th July 2017) - Parodis, I; Ding, H; Zickert, A; Arnaud, L; Larsson, A; Svenungsson, E; Mohan, C; Gunnarsson, I
Abstract : Objectives : We investigated the performance of soluble tumour necrosis factor receptor-2 (sTNFR2) as a biomarker of renal activity, damage, treatment response, and long-term outcome in lupus nephritis (LN). Method : Serum sTNFR2 levels were assessed in 64 LN patients (52 proliferative, 12 membranous) before and after induction treatment, and in 314 non-lupus controls. In LN patients, renal biopsies were performed at baseline and post-treatment. Patients with ≥ 50% reduced proteinuria, normal or improved estimated glomerular filtration rate (eGFR) by ≥ 25%, and inactive urinary sediment were considered clinical responders (CRs). Patients with ≥ 50% improved renal activity index were considered histopathological responders (HRs). Long-term renal outcome was determined using the chronic kidney disease (CKD) stage after a median follow-up of 11.3 years. Results : sTNFR2 levels were elevated in LN patients versus controls both at baseline (p < 0.001) and post-treatment (p < 0.001), and decreased following treatment (p < 0.001). Baseline sTNFR2 correlated with Chronicity Index scores in both baseline (r = 0.34, p = 0.006) and post-treatment (r = 0.43, p < 0.001) biopsies. In membranous LN, baseline sTNFR2 levels were higher in CRs (p = 0.048) and HRs (p = 0.03) than in non-responders, and decreased only in CRs (p = 0.03). Both baseline (p = 0.02) and post-treatment (p = 0.03) sTNFR2 levels were associated with decreasing eGFR throughout long-term follow-up, and post-treatment levels were higher in patients with long-term follow-up CKD stage ≥ 3 versus 1–2 (p = 0.008). Conclusions : Our data suggest serum sTNFR2 as a marker of kidney tissue damage and a predictor of long-term prognosis in LN, and merit further evaluation of sTNFR2 as a predictor of clinical and histopathological treatment outcomes in membranous LN.